Effect of Variations in Acetic Acid Concentration on the Physicochemical Characteristics of Sweet Potato Starch Isolation Results - Aristha, Marcel; Saraswati, Ni Luh Putu Ananda (Jurnal Beta Kimia, 2026)
This study aims to analyze the effect of variations in acetic acid concentration (0; 0.5; 1; 1.5; and 2%) on the physicochemical characteristics of starch. The parameters analyzed included moisture content, water absorption, swelling power, and solubility, as well as structural characterization using Fourier Transform Infrared (FTIR). Data analysis was carried out with one-way ANOVA at a significance level of 5%. The results showed that the variation in acetic acid concentration had a significant effect on water content and swelling power (p < 0.05). The value of swelling power increases at certain concentrations and decreases at higher concentrations, indicating a change in the granules. Conversely, water absorption and solubility were not significantly different (p > 0.05). FTIR analysis showed that the addition of acetic acid did not cause covalent chemical modifications, but rather only affected the physical interactions and hydrogen bonds of starch granules.